Root biomass of Quercusilex in a montane Mediterranean forest - Canadell, Josep; Rodà, Ferran (Canadian Journal of Forest Research, 1991)
Biomass allocation to roots was studied in holm oak (Quercusilex L.), a dominant evergreen tree in broad-leaved sclerophyllous Mediterranean forests. The root systems of 32 single-stemmed holm oaks growing in shallow soils on largely unfissured bedrock were excavated in a mesic site and a xeric site in the Montseny Mountains (northeast Spain). Individual root:shoot biomass ratios (roots with diameter <1 cm not included) of single-stemmed trees were significantly higher in the xeric site (mean 0.45) than in the mesic site (mean 0.37), probably reflecting the lower water availability and higher light availability in the xeric site. It is concluded that single-stemmed holm oaks have higher root:shoot ratios than most temperate forest trees, particularly so when growing on a xeric site. Root:shoot ratios of single-stemmed trees were not linearly correlated with dbh. Allometric regressions of root biomass on dbh did significantly differ between sites. Roots <1 cm in diameter were sampled with soil cores in the mesic site. Holm oaks ≥5 cm dbh in a stand dominated by single-stemmed trees on the mesic site had an aboveground biomass of 160 t/ha and a belowground biomass of 63 t/ha. The belowground biomass was composed of 30 t/ha of root crowns plus roots >5 cm in diameter, 17 t/ha of roots 1–5 cm in diameter, and 16 t/ha of roots <1 cm in diameter. The xeric stand was dominated by multistemmed holm oaks with massive root crowns developed after repeated coppicing. Three multistemmed trees were excavated, yielding a mean root:shoot ratio of 1.2. Through resprouting from root crowns, managed or disturbed holm oak forests can accumulate a belowground biomass greater than that displayed aboveground: 91 t/ha (excluding roots <1 cm in diameter) and 79 t/ha, respectively, in our xeric stand.
doi: 10.1139/x91-245